(untitled) (Carte Romanze, 2021)
the paper verifies some of the most particular stylistic and lexical aspects of the Italian of the migrant writers. The proposition of proverbs of the mother tongue (often compared with equivalent Italians), idiomatic phrases that refer to a different system of values and analogies that propose innovative comparators are detected in a transversal manner. Another interesting aspect is the presence of “migratismi”, native language words attested with great frequency in these works. Similar linguistic characteristics are also observable in the literature of the second generations immigrants, demonstrating how the Italian language is enriching with new words, phrases and imaginaries.